Incidence and predictors of mortality among HIV positive children on anti-retroviral therapy in the selected health facilities of West Wollega Zone, Western Ethiopia: Retrospective cohort study. - Gelane Gurmu; Emiru Merdassa; Gemechu Tiruneh; Keneni Efrem; Firezer Belay; Lalisa Mekonnen; Jira Wakoya Feyisa; Matiyos Lema; Adisu Tafari Shama; Markos Desalegn (PLoS ONE)
Introduction The mortality rate among Human immunodeficiency Virus (HIV) who have started antiretroviral therapy (ART) continues to be increased in resource-limited countries, despite a decline in developed nations. Furthermore, research within this age group is limited and has not previously been conducted in the study area. Consequently, this study aimed to determine the incidence of mortality and its predictors among HIV-positive children who have been receiving ART at public health facilities in West Wollega. Objective To assess incidence rate and predictors of mortality among HIV-positive children on ART at selected health facilities of West Wollega, Ethiopia, 2022. Methods A retrospective cohort study design was conducted. A simple random sampling method was employed to select 286 children living with HIV who started ART from 01 January 2012 to 31 October 2021. Data were entered into Epi-Data Version 3.1, and STATA Version 14 was used for statistical analysis. A Kaplan-Meir survival curve and Long Rank test were used to estimate survival probability and assess statistical differences. The Cox regression model was used to determine independent predictors of mortality. Results The total follow-up time was 15, 652 child-months, and the overall incidence of mortality was 1.92 (95%CI: 1.34, 2.74) per 1000 child-months. The median time to death following the initiation of ART was 6 months. This study also showed that children with WHO clinical stage III (AHR = 3.4, 95% CI: 1.2, 7.4), stage IV (AHR = 5.4, 95%CI: 1.5, 19.8), Being anemic (AHR = 4.9, 95%CI: 1.8, 13.4), CD4 cell count below threshold (AHR = 3.7, 95%CI = 1.4, 9.5), delayed developmental milestone (AHR = 4.5, 95%CI: 1.7, 11.7) were at higher risk of mortality. Conclusion The overall mortality rate was lower compared to the previous study findings. Anemia, WHO clinical stage, CD4 cell count, and delayed developmental milestones were independent predictors of mortality. Therefore, the focus should be given to all children on ART during the early periods of ART initiation, advanced HIV disease, presence of anemia, severe immune deficiency, and delayed developmental milestones.